A Tat-conjugated Peptide Nucleic Acid Tat-PNA-DR Inhibits Hepatitis B Virus Replication In Vitro and In Vivo by Targeting LTR Direct Repeats of HBV RNA - Zhengyang Zeng; Shisong Han; Wei Hong; Yange Lang; Fangfang Li; Yongxiang Liu; Zeyong Li; Yingliang Wu; Wenxin Li; Xianzheng Zhang; Zhijian Cao (Elsevier, 2016)
Hepatitis B virus (HBV) infection is a major cause of chronic active hepatitis, cirrhosis, and primary hepatocellular carcinoma, all of which are severe threats to human health. However, current clinical therapies for HBV are limited by potential side effects, toxicity, and drug-resistance. In this study, a cell-penetrating peptide-conjugated peptide nucleic acid (PNA), Tat-PNA-DR, was designed to target the direct repeat (DR) sequences of HBV. Tat-PNA-DR effectively inhibited HBV replication in HepG2.2.15 cells. Its anti-HBV effect relied on the binding of Tat-PNA-DR to the DR, whereby it suppressed the translation of hepatitis B e antigen (HBeAg), HBsAg, HBV core, hepatitis B virus x protein, and HBV reverse transcriptase (RT) and the reverse transcription of the HBV genome. Furthermore, Tat-PNA-DR administered by intravenous injection efficiently cleared HBeAg and HBsAg in an acute hepatitis B mouse model. Importantly, it induced an 80% decline in HBV DNA in mouse serum, which was similar to the effect of the widely used clinical drug Lamivudine (3TC). Additionally, a long-term hydrodynamics HBV mouse model also demonstrated Tat-PNA-DR's antiviral effect. Interestingly, Tat-PNA-DR displayed low cytotoxicity, low mouse acute toxicity, low immunogenicity, and high serum stability. These data indicate that Tat-PNA-DR is a unique PNA and a promising drug candidate against HBV.